Notes on the origin and evolution of the Corporation - Payet Puccio, José Antonio (2023)
This paper takes a historical overview in order to elucidate the precedents and evolution of one of the most revolutionary and useful organizational instruments in society. From the perspective of many entrepreneurs, the modern corporation is the one that offers the best conditions for the development of business activity.Therefore, the author highlights the importance of analyzing that this institution is built from a long process of development of liability protection mechanisms that, in accordance with the needs of the mankind and with the help of codification, led to what we know today.